Narasi Politik dan Identitas: Pola Penyebaran dan Penerimaan Radikalisme dan Terorisme di Jawa Tengah - Iman Fadhilah; Syaifuddin Syaifuddin; Retno Mawarini (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
This study basically discusses the narration map of Islamism, pattern of its dissemination, acceptance of its narration, and the facilitating factors of the growth of Islamism in Central Java. It is the fact that in the last few years the understanding of Islamism tends to the extremism, radicalism and terrorism. This is an ethnographic study in which it tries to understand the life of individual as part of the community in the wider context. Subjects of this research are; (1) youth; and (2) public figures. Findings of this research are; firstly, although Central Java is well-known as the home ground of radical-terrorism movement, people in this province are actively involved in countering narration of Islamism. Secondly, pesantren (Islamic boarding school), mosques, and religious scholars are elements that play as the front guard of anti-radicalism, extremism and terrorism in Central Java. Thirdly, the youth plays as an important element in articulating of Islamism. This social group is the most vulnerable group who might be influenced by Islamism specifically related to radicalism and extremism